B cell growth and differentiation induced by supernatants of transformed epithelial cell lines. - Rawle, F; Shields, J; Smith, S; Iliescu, V; Merkenschlager, M; Beverley, P; Callard, R (1986)
Growth and differentiation of B cells is thought to be regulated by soluble factors derived from T cells. However, human T cell lines and hybridomas have proved to be notoriously unreliable and unstable sources of such factors. We report here that three stable human bladder carcinoma cell lines T24, RT4 and 5637 produce, in a constitutive fashion, factors which promote growth and differentiation of human B cells.